The future of corporate universities : how your company can benefit from value and performance-driven organisational development - Dealtry, T. Richard (Emerald Publishing Limited, 2017)
Comments on the Research Findings1.1.1.1: Funding; Guide Notes; Summary Comments on the Research Findings; 1.2: Strategic Direction and Policy; Guide Notes; Summary Comments on the Research Findings; 1.3.2: Learning Technologies; Guide Notes; Summary Comments on the Research Findings; 1.3.3: Intellectual Partnerships; Guide Notes; Summary Comments on the Research Findings; 2.0: Marketing Functions - Internal and External; Guide Notes; Summary Comments on the Research Findings; 3.0: Management and Administration; Guide Notes; Summary Comments on the Research Findings.